The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.15261/serdj.19.69
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Separation of Rare Earth Metal Ions with DODGAA in Ionic liquids

Abstract: In order to apply ionic liquids (ILs) to the separation of rare earth metals, liquid-liquid extraction of a series of rare earth elements into the ILs was investigated mainly using 1-octyl-3-methylimidazolium bis(trifluoromethyl sulfonyl) imide, [C 8 mim][Tf 2 N], withN,N-dioctyldiglycol amic acid (DODGAA) as the extractant. A higher selectivity was exhibited for the heavier rare earth elements as in the n-dodecane system, and the order of the extractability of Y(III) in the IL system, situated in the heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…As for the middle rare earth, Eu, the extraction efficiency in both systems was similar. Similar behavior wherein the selectivity between light and heavy rare-earth ions was increased in the ILs compared to that in the organic solvent was observed for other extractants such as PC-88A and recently developed DODGAA (N, N-dioctyldiglycol amic acid) [8,18].…”
Section: Extraction Of Rare-earth Ions With Ho8qsupporting
confidence: 64%
“…As for the middle rare earth, Eu, the extraction efficiency in both systems was similar. Similar behavior wherein the selectivity between light and heavy rare-earth ions was increased in the ILs compared to that in the organic solvent was observed for other extractants such as PC-88A and recently developed DODGAA (N, N-dioctyldiglycol amic acid) [8,18].…”
Section: Extraction Of Rare-earth Ions With Ho8qsupporting
confidence: 64%
“…The liquid-liquid extraction and liquid-membrane transfer of rare-earth metal ions from aqueous solutions containing base metal ions were performed using DODGAA, which indicated that DODGAA has higher selectivity for rare-earth metal ions than for base metal ions. [28][29][30][31] In the present study, we comprehensively investigated the extraction behavior of all Ln 3+ ions, except Pm 3+ , with DODGAA, and investigated the extraction mechanism using slope analysis, loading tests, and electrospray ionization mass spectrometry (ESI-MS) measurements. The mutual separation of individual Ln 3+ ions using DODGAA was compared with mutual separation using D2EHPA (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…DODGAA is expected to be useful for the separation of rare-earth metal ions from foreign metal ions 9,10 as well as the mutual separation of individual rare-earth metal ions from each other. 7,8,12,23 The extractability of Sc(III) gradually increased compared with that of the other rare-earth metal ions. In fact, the slopes of the logarithmic distribution ratio versus the pH were approximately 3 for all rare-earth metal ions, except for Sc(III), and the slope for Sc(III) was 1.08, which is not equivalent to the valence of Sc(III).…”
Section: Resultsmentioning
confidence: 99%